APP educativas y su impacto en el aprendizaje del vocabulario de inglés en los estudiantes del 9no año de EGB de la Unidad Educativa "28 de Mayo" período 2024 -2025 - Chiriguayo Pereira, Adrian Arturo (2025)
The present research analyzed the impact of the use of educational applications on the learning of English vocabulary in students of the 9th year of Basic General Education (EGB) of the "28 de Mayo" Educational Unit. A mixed methodological design was used, combining quantitative and qualitative approaches. Data collection included a pre- and post-intervention diagnostic test, student questionnaires, and teacher interviews. The results showed a significant improvement in the academic performance of the students after using the applications. In the pre-test, only 17% of the students reached an Excellent level, while in the post-test, this percentage increased to 50%. Additionally, the percentage of students needing improvement decreased from 30% to 4%. The questionnaires revealed that 83.33% of students felt more motivated to learn English using applications, and the same proportion expressed preferring these tools over traditional methods. Teacher interviews indicated that apps such as Duolingo, Quizlet, and Kahoot facilitated vocabulary acquisition through interactivity and constant practice. However, teachers also pointed out challenges such as technological dependency and the need to integrate these tools with traditional pedagogical strategies. It was concluded that the educational applications had a positive impact on the acquisition and retention of vocabulary in English, by improving the motivation, active participation and autonomy of the students. However, its effectiveness depended on adequate integration into the curriculum and teacher support during the learning process.